EVALUATION OF THE CHANGE IN LUMINOSITY AND SENSITIVITY IN LASER-ASSISTED TEETH WHITENING: A RANDOMIZED CONTROLLED CLINICAL TRIAL - de Jesús, Erica de Jesús (2025)
Objective: To evaluate the effectiveness of laser-assisted dental bleaching on color luminosity and dental sensitivity. Methods: Twenty-eight patients (75% female, 25% male) with a mean age of 21.75 years were randomly allocated into two groups: experimental and control (n = 14). Both groups received 35% hydrogen peroxide. In the experimental group, the bleaching gel was activated with a 980 nm diode laser at an energy density of 86.41 J/cm² (three applications), whereas the control group did not receive laser activation. Standardized photographs were taken to evaluate luminosity at the middle third of the right maxillary central incisor, using CIELab coordinates at three time points: baseline, immediately after treatment, and at 7 days post-treatment. Dental sensitivity was assessed using a visual analog scale (VAS). Data were analyzed using Mann-Whitney U and Student’s t-tests (p < 0.05). Results: No statistically significant differences in immediate post-treatment luminosity were found between groups (p = 0.412); however, significant differences were observed at 7 days (p = 0.000), with the laser group exhibiting greater color stability. Although sensitivity differences were not statistically significant (p > 0.05), lower VAS scores at 1 and 24 hours were recorded in the experimental group, indicating reduced hypersensitivity. Conclusion: Laser-assisted bleaching with a 980 nm diode laser improves the stability of color luminosity at 7 days, offering clinically relevant benefits. While sensitivity did not show statistically significant differences, the reduced discomfort reported in the laser group highlights its potential to enhance the overall patient experience.